Analysis of Students' Difficulties in Determining Intrinsic Elements in Fairy Stories in Grade 3 Elementary School - Layli, Yunita Afni Nur; Bakhtiar, Afakhrul Mashub (Universitas Trunojoyo Madura, 2023)
This study uses a quantitative descriptive. Data collection was carried out using a test which contained descriptions of students and the results of interview with one of the class 3B homeroom teacher. From the analysis carried out by the researcher, it was shown that from 18 students, most of them had the abilities that were considered good, 4 students with a percentage of 22.22% in the sufficient category and 14 students with a percentage of 77.77% in the good category. Therefore, the overall average score of students in identifying intrinsic elements in fairy tales is 92,75. Basic competence 3.8 Contains about explaining the moral message of fairy tales that are told orally, graphically, or in writing for the purpose of entertainment. And basic competence 4.8 Contains about applying the message in fairy tales as a means of self-expression while using clear phrases and general vocabulary on theme 2 sub-theme 1 in class 3B Minu Sukodono Gresik is in the good category. However, there are factors that can affect students' difficulties in identifying intrinsic elements in fairy tales, including a lack of interest in reading, class conditions that are not conducive, students' memory is low, and students' concentration in reading is less than optimal. In addition, to make it easier for students to analyze intrinsic elements, teacher motivate students in reading books, for example by decorating and making classroom reading corners, using various interesting teaching strategies or media in delivering learning materials especially in listening activity to help students understand the elements that exist in fairy tales.